Pemberian Amelioran Terhadap Status Hara, Pertumbuhan dan Produksi Padi di Lahan Gambut Dataran Tinggi - Muhammad Fikri Ridho; Sarifuddin Sarifuddin; Alida Lubis (Universitas Sumatera Utara, 2014)
This study aims to determine the effect of volcanic sand, sea water and zeolite to nutrient status,growth and yield of dendang rice variety. This research was conducted in highlands peat inHutabagasan, Dolok Sanggul Sub-District Humbang Hasundutan Regency, North Sumatera. Thisstudy used non factorial randomized block design with four treatments are G0 (control), G1(Volcanic sand 5 kg). G2 (Volcanic sand 5 kg + Sea water 2.5 L), G3 (Volcanic sand 5 kg + Seawater 2.5 L + Zeolite 1 kg) and 3 replicants. The treatments G2 and G3 can increase soil electricalconductivity. G3 treatment may act as soil pH buffer. Applications all ameliorant decrease on thenumber of tillers and productive tillers, plant and root dry weight and number of grains each panicleKeywords: Ameliorant, Peat soil, Sea water, Volcanic sand, Zeolite,